Efectos de la cirugía 2-1 en el cultivo de banano - Bustamante Mena, Roberto Carlos (2005)
In the sector The marvel where is the country property of the same name, during the period of Julio the 2005 until October of the same year, you study the effect of the surgery 2-1 in the banana tree cultivation. Inside which you/they thought about the following objectives: 1. To determine the difference of the surgery 2-1 with regard to the degree of the fruit in front of the traditional method. 2. To establish the difference in the yield for cluster. For that which I take two treatments the first one that is the traditional of the country property or considered as witness or surgery 1-1, while the other one is the implanted method or considered as surgery 2-1. After having taken the respective data of the variables analyzed completely by means of the design randomized and compared their averages with Test from T(DLS to 1%) you could conclude the following thing: The implementation of the pruning of the lateral fingers of the surgery 2-1 of the cluster influenced positively when increasing the useful weight of the cluster in 11% and a difference in the reduction of 6% taking like reference the absolute witness. The useful yield for cluster was superior with the pruning, being achieved an increment of 11%. With the pruning it was achieved that 73.3% of the clusters reached the court degree a weeks 11 and 12. The degree or caliber of the fruit in second o'clock and last hand was similar in the treatment surgery and the absolute witness.